Features of the chinese network literature - А.П., Бисенбaевa; Н., Абдурaқын; С.М., Луо (Journal of Oriental Studies, 2019)
The article discusses the history of the development of network literature in China, as well as its place in modern society. Modern literature has lost its homogeneous nature, divided into the one that exists in the traditional form of paper literature, and the one that develops in the network format. Some researchers of online literature associate the story of its origin with the emergence of universal electronic libraries and the digitization of world literature. The proposed article identifies the positive and negative aspects of the development of network works, the main problems of popularizing this area in the literature. Based on the two most popular Chinese sites, an analysis was conducted to identify the most widely read works in the network and the most popular genres in modern China, such as fantasy, fantasy and romance. Today, “online literature” can already be considered as a definite historical stage: it did not generate any significant artistic works or new genre models, but it gave impetus to the development of modern literature. In relation to it, it serves as the environment in which the phenomena of the modern literary process are formed. Key words: China, web literature, online literature in China, modern Chinese writers, web literature genres, problems of web literature development, Chinese culture.